2010
DOI: 10.1159/000315358
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Depressive Symptoms and Patterns of Alcohol Use among College Students

Abstract: Background: Serious alcohol-related negative consequences are associated with a number of drinking behaviors among college students. Thus, it is critical to identify students who are at greater risk for hazardous drinking. Although some studies have shown that depressive symptoms may be associated with alcohol use in this population, findings are not consistent. The current study extends previous research by investigating the relationship between depressive symptoms, daily alcohol use and compulsive drinking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 75 publications
9
35
0
Order By: Relevance
“…This discrepancy could be because Cranford and colleagues (2009) used a binary variable and examined the odds of the presence of frequent HED (HED at least three times in the past 2 weeks), whereas we examined frequency of HED in the past 2 weeks with the possibility of six responses (0, 1 time, 2 times, 3-5 times, 6-9 times, and 10 or more times). This possibility, combined with our previous research indicating that depressive symptoms are associated with daily drinking more in men than in women (Pedrelli et al, 2011), highlights the need for conducting systematic and detailed (not dichotomous yes/no) assessments of heavy alcohol use among students with MDD who may present at health centers or counseling centers. Only a minority of colleges conducts screenings for alcohol misuse (Winters et al, 2011), indicating a need for universities to increase their efforts to identify this risky behavior.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This discrepancy could be because Cranford and colleagues (2009) used a binary variable and examined the odds of the presence of frequent HED (HED at least three times in the past 2 weeks), whereas we examined frequency of HED in the past 2 weeks with the possibility of six responses (0, 1 time, 2 times, 3-5 times, 6-9 times, and 10 or more times). This possibility, combined with our previous research indicating that depressive symptoms are associated with daily drinking more in men than in women (Pedrelli et al, 2011), highlights the need for conducting systematic and detailed (not dichotomous yes/no) assessments of heavy alcohol use among students with MDD who may present at health centers or counseling centers. Only a minority of colleges conducts screenings for alcohol misuse (Winters et al, 2011), indicating a need for universities to increase their efforts to identify this risky behavior.…”
Section: Discussionmentioning
confidence: 94%
“…Findings regarding the association between nonclinical depressive symptoms and alcohol use are also mixed. Among college students, depressive symptoms have been found to be associated with ever engaging in HED (Valentiner et al, 2004), problematic alcohol use (Dvorak et al, 2013), and higher daily alcohol use (Pedrelli et al, 2011) but not with past-month drinking days (Lamis et al, 2010), drinks per month (Gonzalez et al, 2011), weekly drinks (Kenney et al, 2013), and frequent heavy drinking (Lamis et al, 2010;Vickers et al, 2004).…”
mentioning
confidence: 99%
“…Weitzman (2004) found that 81.7% of college students with poor mental health or depression were drinkers, and approximately 50% were heavy episodic drinkers. Furthermore, having greater depressive symptoms is associated with daily alcohol use, alcoholrelated problems, and alcohol use disorders (Dennhardt & Murphy, 2011;Pedrelli et al, 2011;Weitzman, 2004).…”
Section: Depressive Symptoms and Alcohol Usementioning
confidence: 99%
“…Some studies report no signifi cant relationship (Dennhardt and Murphy, 2011;Geisner et al, 2004;Ham and Hope, 2005;Oliver et al, 1998), whereas others link poor mental health-including depression (Pedrelli et al, 2011;Weitzman, 2004), anxiety (Cranford et al, 2009;Terlecki et al, 2011), and stress (Park et al, 2004;Rice and Van Arsdale, 2010)-to greater consumption. It is clear that investigations are needed to examine how poor mental health relates to both alcohol consumption and consequences as well as the extent to which consumption may mediate the link between mental health and consequences.…”
Section: Mental Health and Alcohol Usementioning
confidence: 99%